Morphological similarity of a tri-block copolymer processed at ambient and elevated temperatures - İnceoğlu, Şebnem; Aytun, Taner; Menceloğlu, Yusuf Z.; Özen, İlhan; Acar, Metin H. (Springer Science and Business Media LLC, 2012)
We investigated the effect of temperature on the morphology of a tri-block copolymer (BCP) processed in a capillary rheometer. The material used was a polystyrene-b-poly(2-ethylhexyl acrylate)-b-polystyrene (PS-b-PEHA-b-PS) tri-block copolymer, which was synthesized by ATRP with a molecular weight of 38.5 K consisting of 49 molar % PEHA. According to the rheological data obtained with dynamic viscoelastic oscillatory measurements, order-disorder temperature (ODT) of the BCP was measured at around 110°C. Considering this observation, the samples were studied under different temperatures and pressures (from 110°C to 28°C and from 48 to 75 bar) in capillary rheometer. All processed materials were characterized by using differential scanning calorimetry (DSC) and atomic force microscopy (AFM). It was found that all samples processed by aid of either temperature or pressure showed similar mixed morphologies (a mixture of the ordered and disordered structures i.e., the reduction of microphase separation due to processing).
Keywords: TA401-492 Materials of engineering and construction. Mechanics of materials